Implementation of Risk Assessment and its Challenges in Improving Occupational Safety on MT. Panderman - Moh. Davin Uzza; Iskandar; Tagatorop, Agus Leonard (Politeknik Ilmu Pelayaran Semarang, 2025)
Occupational safety assessment (risk assessment) is a crucial aspect of the maritime industry due to the high potential hazards faced by crew members. This study aims to analyze the implementation of risk assessment in improving occupational safety aboard MT. Panderman, with a focus on risk identification and the effectiveness of control measures in areas such as the engine room, deck, and cargo handling operations. The research employed a qualitative approach, utilizing data collection methods including interviews, observations, documentation, and questionnaires. The analysis involved hazard identification, risk level assessment using a risk matrix, and evaluation of control measures. Data validity was ensured through source triangulation. The findings indicate that the implementation of risk assessment requires collaboration between the captain, officers, and all crew members through toolbox meetings to thoroughly identify operational challenges. Company support in the form of vessel audits, spare parts provision, and routine maintenance is essential. Moreover, crew discipline and understanding of safety procedures (SOPs) are key factors in establishing a safe working environment. This study is expected to serve as a reference for the continuous improvement of occupational safety on board MT. Panderman.